The Influence of Intensive Reading Strategies on the Comprehension of Academic Texts among PJKR UNESA Students - Qooniah Qooniah; Afwa Isnainiyah; Maheswari Cheryl Adiningrum; Felya Nevandita; Alfarel Bintang Putrananda; Trinil Dwi Turistiani (The Future of Education Journal, 2026)
Critical reading ability is a crucial foundation for university students to comprehend complex scientific literature. This study aims to examine the effect of intensive reading strategies on academic text comprehension among students of the Physical Education, Health, and Recreation (PJKR) study program at Universitas Negeri Surabaya (UNESA). Utilizing a quantitative approach with a quasi-experimental one-group pretest-posttest design, this study involved one class of PJKR UNESA students as experimental subjects selected through purposive sampling technique. Data collection was carried out digitally via the Google Form platform, where students' initial ability was measured first (pretest) before being given an intensive reading strategy intervention, and then re-tested at the final stage (posttest). The data analysis technique was carried out simply by comparing the mean scores between the two tests assisted by Microsoft Excel and SPSS. The results showed a significant increase in the mean score of reading comprehension from the pretest stage to the posttest stage. Based on this direct comparison, it can be concluded that the implementation of intensive reading strategies provides a concrete positive influence in improving students' abilities to identify main ideas, understand scientific terms, and construct argument conclusions from academic texts.